High PARP-1 expression predicts poor survival in acute myeloid leukemia and PARP-1 inhibitor and SAHA-bendamustine hybrid inhibitor combination treatment synergistically enhances anti-tumor effectsResearch in context - Xia Li; Chenying Li; Jingrui Jin; Jinghan Wang; Jiansong Huang; Zhixin Ma; Xin Huang; Xiao He; Yile Zhou; Yu Xu; Mengxia Yu; Shujuan Huang; et al. (EBioMedicine, 2018)
Background: PARP-1 plays a critical role in DNA damage repair and contributes to progression of cancer. To explore the role of PARP-1 in acute myeloid leukemia (AML), we analyzed the expression of PARP-1 in AML and its relation to the clinical prognosis. Then, we investigated the efficacy and mechanism of PARP inhibitor BMN673 (Talazoparib) combined with NL101, a novel SAHA-bendamustine hybrid in vitro and in vivo. Methods: The expression of PARP-1 in 339 cytogenetically normal AML (CN-AML) cases was evaluated using RT-PCR. According to the expression of PARP-1, the clinical characteristics and prognosis of the patients were grouped and compared. The combination effects of BMN673 and NL101 were studied in AML cells and B-NSG mice xenograft model of MV4-11. Findings: We found patients in high PARP-1 expression group had higher levels of blast cells in bone marrow (P = .003) and white blood cells (WBC) in peripheral blood (P = .008), and were associated with a more frequent FLT3-ITD mutation (28.2% vs 17.3%, P = .031). The overall survival (OS) and event free survival (EFS) of the high expression group were significantly shorter than those in the low expression group (OS, P = .005 and EFS, P = .004). BMN673 combined with NL101 had a strong synergistic effect in treating AML. The combination significantly induced cell apoptosis and arrested cell cycle in G2/M phase. Mechanistically, BMN673 and NL101 combinatorial treatment promoted DNA damage. In vivo, the combination effectively delayed the development of AML and prolonged survival. Interpretation: High PARP-1 expression predicts poor survival in CN-AML patients. The synergistic effects of PARP inhibitor BMN673 in combination with SAHA-bendamustine hybrid, NL101, provide a new therapeutic strategy against AML. Fund: National Natural Science Foundation of China and Zhejiang Provincial Key Innovation Team. Keywords: PARP-1, Acute myeloid leukemia, PARP inhibitor, SAHA-bendamustine hybrid